Significant accomplishment of the post-disaster housing reconstruction: A community perspective from 2015 earthquake affected communities in Nepal - Suvedi, Mukti (Contemporary Research: An Interdisciplinary Academic Journal, 2020)
In spite of the significant grants and supports after 2015 earthquake, housing reconstruction faced numerous challenges in addressing the needs of the disaster affected communities. The earthquake threatened almost all aspects of the societies in14 of the most affected districts. Government of Nepal and various development partners, including bilateral agencies, were involved in the implementation of housing reconstruction projects in different districts. All these initiatives in communities yielded diverse results. Because of the resulting disquiet from the public, the post-disaster housing reconstruction is becoming the concern and dilemma to researchers, development and humanitarian organizations worldwide. It is evident that private housing reconstruction is complicated and slow process, which is knotted with social, economic, and political dimensions. The paper highlights the significant contributing factors for accomplishing the housing reconstruction after the earthquake. A multi-dimensional holistic approach interprets the nexus of successful reconstruction, which are discussed in the paper. This paper serves as a valuable resource that highlights the significant factors for the government, development and humanitarian partners, and researchers.